2000
DOI: 10.1128/jb.182.18.5139-5146.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Escherichia coli ubiB , a Gene Required for the First Monooxygenase Step in Ubiquinone Biosynthesis

Abstract: It was recently discovered that the aarF gene in Providencia stuartii is required for coenzyme Q (CoQ) biosynthesis. Here we report that yigR, the Escherichia coli homologue of aarF, is ubiB, a gene required for the first monooxygenase step in CoQ biosynthesis. Both the P. stuartii aarF and E. coli ubiB (yigR) disruption mutant strains lack CoQ and accumulate octaprenylphenol. Octaprenylphenol is the CoQ biosynthetic intermediate found to accumulate in the E. coli strain AN59, which contains the ubiB409 mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 46 publications
1
99
0
1
Order By: Relevance
“…Even though little is known about functions of the plastoglobule ABC1-like kinases in plants, the prototypical function of this family is the regulation of ubiquinone metabolism in bacteria and mitochondria (Lundquist et al 2012a). Their mutation leads to accumulation of a ubiquinone precursor and to a shortage of ubiquinone (Cardazzo et al 1998;Leonard et al 1998;Poon et al 2000). In S. cerevisiae, abc1 mutants have a mitochondrial respiratory defect that can be rescued by the addition of exogenous quinones (Bousquet et al 1991;Brasseur et al 1997).…”
Section: Abc1-like Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though little is known about functions of the plastoglobule ABC1-like kinases in plants, the prototypical function of this family is the regulation of ubiquinone metabolism in bacteria and mitochondria (Lundquist et al 2012a). Their mutation leads to accumulation of a ubiquinone precursor and to a shortage of ubiquinone (Cardazzo et al 1998;Leonard et al 1998;Poon et al 2000). In S. cerevisiae, abc1 mutants have a mitochondrial respiratory defect that can be rescued by the addition of exogenous quinones (Bousquet et al 1991;Brasseur et al 1997).…”
Section: Abc1-like Kinasesmentioning
confidence: 99%
“…Moreover, ABC1 is able to complement the coq8 mutant that is defective in ubiquinone synthesis (Do et al 2001). In bacteria, the ubiB gene homolog of ABC1 is required for the first monooxygenase step in ubiquinone synthesis (Poon et al 2000). In humans, mutation of an ABC1-like homolog leads to neuromuscular defects such as ataxia (Mollet et al 2008).…”
Section: Abc1-like Kinasesmentioning
confidence: 99%
“…1). In 2000, Poon et al [19] reported that yigP gene composed of an operon with ubiE and ubiB gene and co-transcribed by the promoter upstream of ubiE gene. In this study, we described a new sRNA gene, named esre (essential sRNA in E. coli), which located within the downstream of yigP gene.…”
Section: Introductionmentioning
confidence: 99%
“…Because possible connections between Abc1 proteins, electron transport, and ubiquinone (plastoquinone and phylloquinone) synthesis have been postulated (Poon et al, 2000), we performed analysis of electron transport in AtOSA1 mutants. The kinetic measurements of Chla fluorescence probing the redox state of the primary quinone acceptor of PSII and 820 nm transmission probing the redox state of mainly plastocyanin and P700 (reaction center chlorophylls of PSI) revealed no differences between atosa1-1 and the wild type (data not shown).…”
Section: The Effect Of Light On Atosa1 T-dna-inserted Mutantsmentioning
confidence: 99%
“…However, more recent data suggest that the ABC1 protein might be implicated in the regulation of coenzyme Q biosynthesis (Hsieh et al, 2004). The Abc1 family has also been described as a new family of putative kinases (Leonard et al, 1998), and it has been suggested that the putative kinase function of Abc1-like proteins is related to the regulation of the synthesis of ubiquinone (Poon et al, 2000). Homologs of yeast ABC1 have been isolated in higher eukaryotes.…”
mentioning
confidence: 99%